2019
DOI: 10.3390/ijerph16081468
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress among Caregivers of Children with Autism Spectrum Disorder: A State-Wide Study

Abstract: Background: Caregivers of children with autism spectrum disorder (ASD) experience increased stress and more significant negative caregiving consequences than those with typically developing children. There is a lack of studies specifically focusing on stress among caregivers with ASD children in Asian countries. The current study examines levels of perceived stress and factors associated with it among caregivers in Kelantan, Malaysia. Methods: In a cross-sectional study, the Malay version of the Perceived Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 20 publications
3
15
1
1
Order By: Relevance
“…The current study also characterized caregiver mental health, and in particular stress and anxiety, during COVID-19, that is, caregiver perceptions of their current (Ersoy et al, 2020;Esentürk, 2020;Manning et al, 2020;Pavlopoulou et al, 2020;Stankovic et al, 2020;White et al, 2021), the majority of participants in the sample indicated that they were experiencing moderate levels of stress and high anxiety, and the majority of caregivers were low in resilient coping. Caregiver perceived stress in the present sample appears to be comparable to that of caregivers of autistic individuals prior to COVID-19 also measured using the PSS-10 (Lovell & Wetherell, 2016;Nik Adib et al, 2019). Compared to prepandemic stress, stress of caregivers of neurotypical children (measured using the PSS-10) has increased overtime during COVID-19 (Adams et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…The current study also characterized caregiver mental health, and in particular stress and anxiety, during COVID-19, that is, caregiver perceptions of their current (Ersoy et al, 2020;Esentürk, 2020;Manning et al, 2020;Pavlopoulou et al, 2020;Stankovic et al, 2020;White et al, 2021), the majority of participants in the sample indicated that they were experiencing moderate levels of stress and high anxiety, and the majority of caregivers were low in resilient coping. Caregiver perceived stress in the present sample appears to be comparable to that of caregivers of autistic individuals prior to COVID-19 also measured using the PSS-10 (Lovell & Wetherell, 2016;Nik Adib et al, 2019). Compared to prepandemic stress, stress of caregivers of neurotypical children (measured using the PSS-10) has increased overtime during COVID-19 (Adams et al, 2021).…”
Section: Discussionsupporting
confidence: 58%
“…1,3 Parents with ASD children also had a high level of stress. 5 In several other studies, it was also stated that mothers of children with ASD experienced more severe problems when compared to mothers of children with physical disabilities, Down's syndrome, or healthy children. This can lead to the emergence of a burden on family members and mothers in particular.…”
Section: Introductionmentioning
confidence: 98%
“…Mothers of children with ASD spend more effort, patience and time on daily duties to meet the high care demands of their children, as well as managing ASD. Besides, the effect of mothering children with ASD is like the disorder itself, multifaceted and pervasive (Adib et al, 2019). Also, the inadequate provision of education and health care services may result in experiencing stress concerning ASD in Egypt.…”
Section: Discussionmentioning
confidence: 99%